The role of lung ultrasound in preterm neonates with respiratory distress in neonatal intensive care unit - Swarup, Sidhant; Panigrahi, Rakesh; Swain, Suryakanta; Agrawal, Hemant (Indian Journal of Child Health, 2021)
Introduction: Up to 29% of late preterm babies suffer from respiratory distress due to which they need to be admitted to neonatal intensive care unit (NICU). Point-of-care ultrasound is a useful tool in critical neonate care, providing valuable information without any risk of ionizing radiation to the newborn. Materials and Method: This mono-centric, descriptive, and prospective study was conducted in NICU. Preterm newborns of less than 36 weeks with respiratory distress at birth on non-invasive ventilation were recruited. A lung ultrasound was performed at first 12 h of life and followed till their discharge. Main outcomes need for surfactant treatment. Results: Sixty preterm infants (median gestational age: 29 weeks) were recruited. Newborn in the surfactant group requiring ultrasound and intervention was significantly higher than in no surfactant group (p